Economic evaluation of biogas plant size utilizing giant reed. (September 2015) - Sgroi, Filippo; Foderà, Mario; Trapani, Anna Maria Di; Tudisca, Salvatore; Testa, Riccardo
Abstract: Amongst energy crops for the production of biomass feedstock for biogas plants, giant reed ( Arundo donax L) has been attracting attention in recent years in Italy. Undoubtedly, this is due to its potentially high yield in terms of biomass, low agronomic inputs, as well as for being eligible for European Union energy crop incentives. The aim of this study was to perform an analysis of plant costs considering three macro-categories (biomass, plant installation and transport). Also, we aimed to describe the economic performances of biogas plants, while progressively altering two key variables. Specifically, we considered electrical power capacity (in the 100–999 kW range) and several combinations of feeding mixtures of livestock waste and giant reed silage, so as to determine the most economically advantageous option for a given power capacity. The results showed, on the one hand, that plants having diverse power capacities entail costs that vary as a function of the feedstock used and, on the other, that the entrepreneur׳s options mainly revolve around two variables, i.e. biomass supply costs and plant size.